Link Between Perception of Treatment Need and Craving Reports in Addiction - Lambert, Laura; Serre, Fuschia; Thirioux, Berangere; Jaafari, Nematollah; Roux, Perrine; Jauffret-Roustide, Marie; Lalanne, Laurence; Daulouède, Jean-Pierre; Auriacombe, Marc (Frontiers in Psychiatry, 2022)
Background: Perception of Treatment Need (PTN), a component of clinical insight, is associated to negative addiction treatment outcomes when low. Our hypothesis was that lower PTN was associated with less craving when reported retrospectively, the most common measure of craving in clinical settings. Objective: To explore the association between PTN and craving among a dataset of subjects with severe substance use disorders. Methods: Participants were recruited from outpatient addiction clinic admissions or harm reduction program services. Good and Low PTN were based on consistency between severe addiction (at least six DSM-5 criteria) and self-report need for addiction treatment from the Addiction Severity Index. Craving was retrospectively characterized over the past 30 days. Multiple regression analyses were conducted. Results: Participants with Low PTN (n=97) retrospectively reported less frequent and intense episodes of craving, compared to participants with Good PTN (n=566) after controlling for sociodemographic factors, addiction type and severity (p<0.0001). Conclusion: Low perception of treatment need among subjects with severe addictions is associated to less retrospective report of craving which may contribute to reduced efficiency of treatment. Further studies are needed to explore the mechanisms of the association.